In-vitro anthelmintic activity of Boswellia serrata and Aloe barbadensis extracts on Pheretima posthuma: Indian earthworm - Shelke, Pallavi Sitaram; Jagtap, Pradnya Nilesh; Tanpure, Prajakta Rohidas (International Journal of Research in Medical Sciences, 2020)
Background: The development of anthelmintic resistance and the high cost of conventional anthelmintic drugs led to the evaluation of medicinal plants as an alternative source of anthelmintics. In the current study, in- vitro experiments were conducted to determine the possible anthelmintic effects of crude aqueous and alcoholic extracts of the resins of Boswellia serrata and leaves of Aloe barbadensis on adult Indian earthworm (Pheretima posthuma). Methods: Various concentrations (50, 100, 150 mg/ml) of each extracts were tested and results were expressed in terms of time for paralysis and time for death of worms. The activities are well compared with the standard drug Albendazole as a positive control and saline water as negative control. Results: Anthelmintic activity was observed as dose dependent manner. It was found that alcoholic extract exhibited maximum anthelmintic activity at concentration 100 and 150 mg/ml compared to standard drug Albendazole (10mg/ml) while aqueous extract show modest significant activity at concentration 150 mg/ml against worm Pheretima posthuma. All results was statistically analysed by using ‘Dunnett’s test’ one- way ANOVA; the p<0.001 were significant when compared with control and standard group. Conclusions: The present study proves the potential of combination of B. serrata and A. barbadensis as an anthelmintic drugs. Further studies are necessary to isolate and reveal the active compounds and to establish the mechanism of action.